NILAI-NILAI PENDIDIKAN DALAM NOVEL SANG PEMIMPI KARYA ANDREA HIRATA: KAJIAN STILISTIKA - Abdul Rochman (EDU-KATA, 2018)
The purpose of this study is to describe: (1) the style of language used in the novel by Andrea Hirata The Dreamer; (2) The educational values ​​used in the novel The Dreamer author. This research is a descriptive qualitative. The method used is descriptive qualitative method. The data source is the novel The Dreamer mold 32nd March 2015 issued by the issuer PT. Library spans Yogyakarta. Data collection techniques using recording techniques. Validity used is triangulation theory. Data analysis technique used is qualitative analysis that includes four components, namely the fireplace of data, reduction, data presentation and conclusion. Based on the analysis of four grades. The educational values, namely: (a) the value of religious education is a viewpoint that bind man to God creator of the universe and everything (b) the value of moral education is a value which measures whether humans should get along in social life, (c) the value of education social awareness and a sustainable emotion relative to an object, idea, or person. (d) the value of cultural education is something that is considered good and valuable by a group or tribe.